The Influence of Work Environment and Motivation on Employee Performance - Inna Nisawati Mardiani; Paskalis Jaya (Journal of Research in Business, Economics, and Education, 2021)
The purpose of this study was to determine the effect of work environment and motivation on employee performance. This study uses quantitative methods. The population and sample in this study were employees of PT. Maxxis International Indonesia is part of the quality control division with a total of 62. The method of data collection is through questionnaires distributed through google form. In conducting data analysis, using the SPSS program. The techniques used in this research are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Test and Hypothesis Testing. The results of the study show that the work environment variable has a significant effect on employee performance, the results of the study on motivational variables have a significant influence on employee performance.